More than rhizosphere colonization of strawberry plants by Azospirillum brasilense - Guerrero Molina, María Fernanda (2012)
Azospirillum brasilense is a plant growth promoting bacteria (PGPB), capable of improving growth and yield of important crops including strawberry (Fragaria ananassa, Duch.). Considering that for commercial purposes strawberry plants are asexually reproduced by planting stolons into the soil, the aim of this work was to evaluate Azospirillum root association and further colonization through stolons from bacterial inoculated strawberry mother-plants to new born daughter-plants. For that, three commercial cultivars of strawberry ('Camarosa', 'Milsei' and 'Selva') were root inoculated with two strains of A. brasilense: REC3 and PEC5. Scanning and transmission electron microscopy observations showed clear bacterial attachment to the root surface and colonization of root and stolon inner tissues. The diazotrophic bacteria were re-isolated from inoculated mother-plants, non-inoculated daughters and stolons using N-free NFb semisolid medium. In all cases, the MPN from root samples was higher than from stolons. The bacterial nifD gene, essential in the biological N 2-fixing process, was PCR-amplified from DNA of roots and stolons proving the occurrence of diazotrophs within these tissues. To confirm that these bacteria corresponded to the inoculated PGPB, the 16S rDNA gene of re-isolates was subjected to amplified rDNA restriction analysis (ARDRA) and to automated DNA sequencing, revealing that they belong to Azospirillum brasilense. This confirms effective rhizosphere colonization of strawberry mother-plants and also the colonization of A. brasilense to new daughter-plants via stolons. This is the first report about A. brasilense colonization from one strawberry plant to another one by colonizing inner tissues of roots and stolons. This means that a single inoculation with selected PGPB would allow the growers to have numerous plant generations at nursery already inoculated and with better conditions to be planted at field, contributing to a sustainable agricultural practice.